Genetic diversity and differentiation in nine West African local goat breeds assessed via microsatellite polymorphism - Missohou, Ayao; Poutya, M.R.; Nenonene, A.; Dayo, G.K.; Ayssiwede, S.B.; Talaki, E.; Issa, Y.; Fane, A. (Elsevier, 2011)
This study was carried out to study the genetic relationship among nine (9) West African goat breeds out of which 6 (Guinea dwarf, Kirdi, Ghana dwarf, Mossi, Togo dwarf, Senegal dwarf) were of the trypanotolerant type and 3 (Mali Sahel, Mauritania Sahel, Chad Sahel) were of the trypanosusceptible type. One hundred ninety nine (199) animals were genotyped using 10 microsatellites. The microsatellites loci analysed were highly polymorphic with a mean number of alleles of 11.7 ± 3.7 ranging from 6 to 20. Observed heterozygosities ranged from 0.603 ± 0.164 (Togo dwarf) to 0.726 ± 0.166 (Chad Sahel). It was lower than expected heterozygosity in most of the breeds indicating a deviation from Hardy Weinberg equilibrium. The Fst measure of genetic distance between pairs of populations showed the highest distance (0.098) between Kirdi and Guinea dwarf which presented an isolated position from the other breeds and the lowest distance (0.025) between Togo dwarf and Mossi. Our study showed that the genetic relationships among the concerned breeds correspond to their geographical distribution. In addition, Guinea dwarf is strongly separated from the other breeds.